(untitled) - VUFO-NGO resource centre (Ha Noi, 2008)
Engagement forms emphasized in the study are the ones that have come to be commonly discussed by government authorities, Communist Party leaders, international donors, and citizen organizations: service delivery, policy and law-making, monitoring and holding official accountable, and channeling citizens’ concerns.The project’s objectives are two-fold. One is to examine some of the shapes of state-civil society engagement that previous studies have referred to but for which little has been empirically studied. The second is to use the findings to make specific recommendations about engagement that will help state authorities and civil society organizations (CSOs) to better understand the nature of their relationships and identify ways to enhance their interactions. The recommendations also aim to help international actors support engagement more effectively.
Keywords: Public administration and public policy,Hành chính và chính sách công